Sheads family papers - Sheads, J. James, -1864.
Correspondence, diary, certificates, reports, and other papers relating to the Sheads family of Pennsylvania and their role the Civil War. Includes diary (1864 February 10-June 25) of J. James Sheads relating to his service with the 21st Pennsylvania Cavalry at the battle of Cold Harbor and siege of Petersburg, Va., and ALS (1863 July 7) written by Lt. Col. Henry G. Tuthill, 104th New York Infantry, on the aid and comfort given his troops by the Sheads family during the battle of Gettysburg.
In part, handwritten transcripts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Tuthill, Henry G. -- Correspondence; Sheads family; United States. -- Army. -- Pennsylvania Cavalry Regiment, 21st (1863-1865); United States. -- Army. -- New York Infantry Regiment, 104th (1862-1865); Cold Harbor, Battle of, Va., 1864.; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Pennsylvania -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Siege, 1864-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- History -- Civil War, 1861-1865 -- Campaigns